(untitled) (International Journal of Engineering and Computer Science, 2017)
Image mosaicing is the act of combining two or more images.It aims to combine images such that no obstructive boundary exists around overlapped regions. Emphasis is given on to create a mosaic image that contains as little distortion as possible from the original images, as well as preserving the general appearance of the original image. Multiresolution representation technique is an effective method for analyzing information contents of signals, as it processes the signals individually at finer levels, to give more accurate results that contains much less distortion. Laplacian pyramid, Gaussian pyramid and Wavelet transform are types of Multiresolution representations. In the proposed work, I have use wavelet transform, Laplacian pyramid using Gaussian pyramid as transforms function in context of simplicity and working satisfactorily in real time domain. Application areas of this subject are widespread in the fields like signal analysis, image coding, image processing, computer vision and still counting. The work in this project will be focused on designing a model which balances the smoothness around overlapped region and the fidelity of blended image to the original image.